Autoimmune thyroid disease in pregnancy - Sailakshmi, M. P. A.; A, Pavana Ganga; BR, Rekha; Akash, Suhasini S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal thyroid dysfunction is the common endocrinological disorder during pregnancy. It is associated with adverse maternal and foetal outcomes like pre-eclampsia, GDM, preterm, IUGR and miscarriage. Objective of this study was to study the prevalence of thyroid dysfunction in women with thyroid autoimmunity and its relation with adverse maternal and foetal outcomes. Methods: It was an observational study undertaken at RRMCH from May-2013 to Oct-2013. Pregnant women were screened for thyroid dysfunction. Women with altered thyroid function tests were screened for anti TPO antibodies. Mothers with thyroid dysfunction and anti TPO antibody positive were compared with anti TPO negative mothers. Results: Study group included 1000 pregnant women, 126 women had hypothyroidism. Anti TPO antibodies were positive in 26 women. Prevalence of hypothyroidism and autoimmunity were 7.5% and 12.8% respectively. 46.2% women with hypothyroidism and thyroid autoimmunity had PE, P value <0.01, 7% had GDM with P value <0.603, 15.4% had IUGR with p value of 0.033.7, 7% women had IUD. Conclusions: Hypothyroidism and thyroid autoimmunity are common during pregnancy. They are associated with adverse maternal and foetal outcome. Screening for thyroid dysfunction and early initiation of treatment can prevent adverse maternal and fetal outcome.